HIV and lupus erythematosus: A diagnostic dilemma - Kaliyadan Feroze (Wolters Kluwer Medknow Publications, 2008)
A 30-year-old female patient presented to us with erythema over the face and raised hyperpigmented, scaly skin lesions, mainly over photo-exposed parts, of about 5-month duration. Based on her clinical features and initial laboratory finding, we considered the possibility of a connective tissue disease. On further follow-up, she was found to be human immunodeficiency virus positive (confirmed by Western blot).